2016
DOI: 10.1590/1807-3107bor-2016.vol30.0113
|View full text |Cite
|
Sign up to set email alerts
|

Marginal and internal fit of zirconia copings obtained using different digital scanning methods

Abstract: The objective of this study was to evaluate the marginal and internal fit of zirconia copings obtained with different digital scanning methods. A human mandibular first molar was set in a typodont with its adjacent and antagonist teeth and prepared for an all-ceramic crown. Digital impressions were made using an intraoral scanner (3Shape). Polyvinyl siloxane impressions and Type IV gypsum models were also obtained and scanned with a benchtop laboratory scanner (3Shape D700). Ten zirconia copings were fabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
6
31
0
1
Order By: Relevance
“…In the included studies, marginal gap from intra‐ and extraoral scanning was between 16 to 80 μm and 19 to 112 μm, respectively. In four studies marginal gap of the restorations made using different intraoral scanners was significantly less than marginal gap of restorations made using extraoral scanners . However, in one study, marginal gap of restorations in either group showed no significant difference …”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In the included studies, marginal gap from intra‐ and extraoral scanning was between 16 to 80 μm and 19 to 112 μm, respectively. In four studies marginal gap of the restorations made using different intraoral scanners was significantly less than marginal gap of restorations made using extraoral scanners . However, in one study, marginal gap of restorations in either group showed no significant difference …”
Section: Discussionmentioning
confidence: 81%
“…Three of the 13 chosen studies reported the marginal gap of restorations made by the impression scanning method. [52][53][54] The results showed that both methods of extraoral scanning will result in a clinically acceptable marginal gap.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…After milling, copings were sintered. Marginal and internal adaptation of each coping was measured using the silicone replica technique (18,23,24) and micro-CT imaging (19,(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%